Frequency of Hepatitis B and C Viral Infection among the Medical Waste Handlers (Bangladesh Journal of Infectious Diseases, 2018)
Background: Chronic viral hepatitis is a major health problem worldwide. Medical waste handlers (MWH) are particularly vulnerable to such hepatitis due to nature of their job.Objective: The purpose of the present study was to see the prevalence of hepatitis B virus and hepatitis C virus infection among the medical waste handlers.Methodology: This cross-sectional study was done from January 2015 to June 2015 to know the frequency Hepatitis B and Hepatitis C among medical waste handlers in SSMC Mitford Hospital, Dhaka. Result: 96 medical waste handlers were enrolled. The mean age was 38.39 (SD ±10.057) years (range: 20 to 60 years). The leading age group was 31-40 years (32%). Most of them had little educational attainment and more than half of the respondents (53.1%) were working in the hospital for more than 10 years. Prevalence of HBV and HCV were 6.3%% and 1% respectively in MWH. More percentage of HBsAg was identified in female (8.1%), in age group between 30-39 years (17.9%), in MWH who were in the service for 7-10 years. 7.2% of the MWHs were found to have needle stick or sharp injuries while 7.7% had mucous membrane contamination. More than three-fourths of the MWHs wore thick disposable gloves, 30 (31.3%) protective gown and only 14 (14.6%) wore boots. Male MWHs were significantly more likely to wear Boots (OR: 1.505: P < 0.002) compared to Female. Conclusion: Due to needle stick puncture infectious disease like Hepatitis B & C can be transmitted to the health care workers. Health education, prophylaxis by vaccination, universal precautions and proper hospital waste management are crucial in the prevention of HBV and HCV infection. Bangladesh Journal of Infectious Diseases 2017;4(1):3-9